2021
DOI: 10.1101/2021.01.01.20249069
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Accuracy of the Veterans Health Administration COVID-19 (VACO) Index for predicting short-term mortality among 1,307 Yale New Haven Hospital inpatients and 427,224 Medicare patients

Abstract: BackgroundThe Veterans Health Administration COVID-19 (VACO) Index incorporates age, sex, and pre-existing comorbidity diagnoses readily available in the electronic health record (EHR) to predict 30-day all-cause mortality in both inpatients and outpatients infected with SARS-CoV-2. We examined the performance of the Index using data from Yale New Haven Hospital (YNHH) and national Medicare data overall, over time, and within important patient subgroups.Methods and findingsWith measures and weights previously … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 30 publications
3
9
0
Order By: Relevance
“…69 In separate analyses, we developed a predictive index based on Veterans Affairs data 70 and have since shown that the risk of covid-19 mortality associated with age, sex, and comorbid disease diagnoses that we observed in Veterans Affairs data was consistent across other academic and national healthcare samples in the US. 71 Our key finding in the current analysis has also been shown in smaller, non-veteran healthcare systems 13 14 ; thus, effects reported in this study are probably generalizable to the wider US population. Fifth, although individuals in Veterans Affairs care represent a diversity of backgrounds, women represented a small proportion of the sample population and thus results might not be generalizable to women.…”
Section: Comparison With Other Evidencesupporting
confidence: 67%
See 1 more Smart Citation
“…69 In separate analyses, we developed a predictive index based on Veterans Affairs data 70 and have since shown that the risk of covid-19 mortality associated with age, sex, and comorbid disease diagnoses that we observed in Veterans Affairs data was consistent across other academic and national healthcare samples in the US. 71 Our key finding in the current analysis has also been shown in smaller, non-veteran healthcare systems 13 14 ; thus, effects reported in this study are probably generalizable to the wider US population. Fifth, although individuals in Veterans Affairs care represent a diversity of backgrounds, women represented a small proportion of the sample population and thus results might not be generalizable to women.…”
Section: Comparison With Other Evidencesupporting
confidence: 67%
“…However, previous research has established that after adjusting for age, sex, race, ethnicity, region, and residence type, all of which were accounted for in this study, total disease burden between veterans and non-veterans does not differ 69. In separate analyses, we developed a predictive index based on Veterans Affairs data70 and have since shown that the risk of covid-19 mortality associated with age, sex, and comorbid disease diagnoses that we observed in Veterans Affairs data was consistent across other academic and national healthcare samples in the US 71. Our key finding in the current analysis has also been shown in smaller, non-veteran healthcare systems1314; thus, effects reported in this study are probably generalizable to the wider US population.…”
Section: Discussionmentioning
confidence: 91%
“… 43 The VACO index can help clinicians make better treatment decisions for veterans with COVID-19, such as determining who should be managed as inpatients who require close clinical follow-up, and even determining who is a priority for COVID-19 vaccination. 44 …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the utility of this score in COVID-19 is not well established. Other scores developed include the VACO Index [4], 4C mortality score 5] and COVID-GRAM [6]. Additionally, scores previously used for non-Covid pneumonia such as CURB-65 have also been tested on COVID-19 patients [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, they often suffer from certain de ciencies, limiting their generalized applicability. For example the VACO index, an otherwise thoroughly investigated and validated score, has signi cantly different Area under the Curves for different subgroups, implying limited generalizability of the score in various populations [4]. Another score, the COVID-GRAM, has good predictive ability in low-risk patients for progression to severe disease, but overestimates risk in high-risk patients [6].…”
Section: Introductionmentioning
confidence: 99%